2020
DOI: 10.32474/ado.2020.03.000156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of The Downregulation of TPD52-Like3 Gene and NKX2-1 Gene in Type 2 Diabetes Mellitus Via RNA Sequencing

Abstract: In an earlier study, it was proposed that the final consequence of hereditary anomaly results in the development of type 2 diabetes, which already emerges in the prediabetic phase. It was thought to occur due to an increased flux, as compared to the healthy controls where protons (H + -ions) from the mitochondrial intermembranespace re-enter the matrix via uncoupling protein-1 (UCP1). This causes hyperthermia in and around the mitochondria [1].But the key question that remains to be answered here is for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…TPD52, TPD52L1, TPD52L2, and TPD52L3 [8,9]. When analyzing TPD52 and TPD52L3 genes, researchers found that the two sequencers shared 63 identical positions and 42 similar positions, resulting in an overall homology of 67.9% (Figure 1) [10]. Indeed, based on the high sequence homology with TPD52L3, it appears plausible that the primary function of TPD52L3 is lipid storage in adipose cells.…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPD52, TPD52L1, TPD52L2, and TPD52L3 [8,9]. When analyzing TPD52 and TPD52L3 genes, researchers found that the two sequencers shared 63 identical positions and 42 similar positions, resulting in an overall homology of 67.9% (Figure 1) [10]. Indeed, based on the high sequence homology with TPD52L3, it appears plausible that the primary function of TPD52L3 is lipid storage in adipose cells.…”
Section: Geneticsmentioning
confidence: 99%
“…These results imply that a decrease in the unsaturation index in individuals with prediabetes or type 2 diabetes mellitus has the potential to translate into an increase in attractive forces between the mutual membrane phospholipid acyl chains, which redistributes the lateral pressure profile of the cell membrane [27]. This redistribution induces alterations in mechanical and biochemical properties of the glucose transport channel proteins, i.e., it reduces the pore diameter, which in turn, reduces the rate of glucose transport across the cell membrane, and therefore causes the onset of type 2 diabetes mellitus [10].…”
Section: Membrane Flexibility and (Pre)diabetes Typementioning
confidence: 99%